Conditions favorables à la reconnaissance des acquis de personnes enseignantes - Bélisle, Rachel; Mottais, Évelyne; Supeno, Eddy; Bibeau, Jean; Bélisle, Marilou; Breton, Stéphanie (Canadian Journal of Education/Revue canadienne de l’éducation, 2023)
This article is intended to support organizations that contribute to the development of recognition of prior learning (RPL) to promote access to regulated professions where there is a shortage. It uses the teaching profession in Quebec as an example. The method is a review of the literature on university RPL published between 2005 and 2021, in nine databases and in the work of organizations active in RPL empirical research. The content analysis framework focuses on the functions and phases of the RPL process in universities, particularly of learning realized in non-formal or informal contexts. The review confirms that this type of recognition can be complex to achieve and that its implementation relies on continuous efforts to allow for a progressive adhesion of the personnel involved and a coherent institutional message. The article suggests avenues for action and research to create favourable conditions for RPL.